A Comparative Study of Feminism and Feminist Approach of Shashi Deshpande with reference to the novel That Long Silence: Exploring Feminist Themes in Shashi Deshpande's That Long Silence (Journal of Advances and Scholarly Researches in Allied Education, 2017)
That Long Silence is a novel written by Shashi Deshpande in which she urges society to break all the norms which it has decided for women. It is not a violent attack on society but a request in silence to break silence to break silence which is a boundary or a mirror or a trend, a sigh or a mark which has been shown by male dominating society to the secondary sex (females). This is a kind of false consciousness in which females are living and thinking themselvesunnecessary and unrequired. This is also a type of self negation which can be analyzed through the character, Jaya, the name given by her father which means victory but her name has been changed by her husband as Suhasini, a domestic ordinary woman whose all the wishes are related her family not for herself. So the theme of my paper is actually about the journey of Jaya from self negation to self assertion. This story is not actually the story of Jaya but the ninety percent of Indian woman are living of the same standard of Jaya. Urbanization and Education are the two factors which cannot work basically for women liberation. Self assertion can be acquired by doing a lot of efforts in the field of awareness. Shashi Deshpande is also doing the same efforts by writing novels on Female issues. This research paper is the comparative study of Shashideshpande’s inquisitiveness of Feminism and her Feminist approach used in That Long Silence.